Education Reform; Between Hope and Reality - Saeful Anam (Academia Publication, 2021)
This article describes the importance of educational reform as an act of innovation and educational renewal, especially in Indonesia. The forms of educational reform are very diverse, one of which is in the form of decisions and policies issued by the government in enforcing provisions in national education, such as curricula, learning models and other policies. However, in carrying out an education reform one must always remember the basis for the implementation of education itself so as not to take wrong actions and result in failure in its implementation